Age-related differences of serum total testosterone and psychological factors in patients with erectile dysfunction - Yang, Zhaoxu; Lu, Chencong; Wang, Qing; Liu, Tao; Xu, Yan; Huang, Xinfei; Chen, Jianhuai (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to explore the differences of the psychological states and total testosterone (TT) in patients with erectile dysfunction (ED) across various age groups.MethodsA total of 1411 ED patients were enrolled from the Department of Andrology, Jiangsu Province Hospital of Chinese Medicine, Affiliated Hospital of Nanjing University of Chinese Medicine from September 2018 to September 2021. The SCL-90 was used to evaluate the psychological condition of patients while the 5-item international index of erectile function (IIEF-5) questionnaire was applied to estimate the severity of ED. The serum TT level of patients was also measured. ED patients were divided into three groups (group A: 20–30 years old; group B: 31–40 years old; group C: 41–50 years old). In addition, patients in each group were divided into three groups including mild group (12<IIEF-5<21), moderate group (8<IIEF-5<11), and severe group (IIEF-5<7). The level of TT and SCL-90 scores were compared between groups. Finally, relationships between SCL-90, STAI scores and TT were explored.Results(1) Differences of TT between groups with different ages: The TT level of group A was higher than that of group B and C (P<0.05). (2) Differences of TT between patients with different ED severity in each age group: The TT level of severe ED patients was lower than that of mild ED patients in group B (P<0.05) while the TT level of severe ED patients was lower than that of mild and moderate ED patients in group C (P<0.05). (3) Differences of SCL-90 and STAI scores between patients with different severity in each age group: The factor scores of anxiety, psychoticism, obsession, interpersonal relationship, depression and total scores of SCL-90 of group A and B were higher than those of group C (P<0.05). (4) Differences of SCL-90 and STAI scores between patients with different severity in each age group: 1) The factor scores of hostility, anxiety, phobia, paranoid, psychoticism, obsession, depression and total scores of SCL-90 of mild ED patients were lower than those of moderate and severe ED patients in group B (P<0.05); 2) The factor scores of anxiety and other of SCL-90, as well as the state anxiety scores of STAI of mild ED patients were lower than those of severe ED patients in group C (P<0.05). (5) The level of TT was positively related to IIEF-5 scores of ED patients (r = 0.06; P = 0.02). Both SCL-90 (r = -0.08; P < 0.01) and STAI (r = -0.06; P = 0.04) scores were negatively associated with IIEF-5 scores of ED patients. STAI scores were positively related to SCL-90 scores of ED patients (r = 0.64; P < 0.01).ConclusionAge-stratified results demonstrate a pronounced differential impact of TT and psychological factors on ED. Compared with younger patients, serum TT has more significant effects on elderly patients with ED. For young ED patients, the influences of psychological factors are significantly higher than that of elderly patients, and young patients show more severe anxiety and depression.